Deficiency of CC chemokine ligand 2 and decay-accelerating factor causes retinal degeneration in mice. (September 2015) - Yu, Minzhong; Kang, Kai; Bu, Ping; Bell, Brent A.; Kaul, Charles; Qiao, James B.; Sturgill-Short, Gwen; Yu, Xiaoshan; Tarchick, Matthew J.; Beight, Craig; Zhang, Sarah X.; Peachey, Neal S.
Abstract: CC chemokine ligand 2 (CCL2) recruits macrophages to reduce inflammatory responses. Decay-accelerating factor (DAF) is a membrane regulator of the classical and alternative pathways of complement activation. In view of the link between complement genes and retinal diseases, we evaluated the retinal phenotype of C57BL/6J mice and mice lacking Ccl2 and/or Daf1 at 12 months of age, using scanning laser ophthalmoscopic imaging, electroretinography (ERG), histology, immunohistochemistry, and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) analysis. In comparison to C57BL/6J mice, mutant mice had an increased number of autofluorescent foci, with the greatest number in the Ccl2 −/− /Daf1 −/− retina. ERG amplitudes in Ccl2 −/− /Daf1 −/−, Ccl2 −/− and Daf1 −/− mice were reduced, with the greatest reduction in Ccl2 −/− /Daf1 −/− mice. TUNEL-positive cells were not seen in C57BL/6J retina, but were prevalent in the outer and inner nuclear layers of Ccl2 −/− Daf1 −/− mice and were present at reduced density in Ccl2 −/− or Daf1 −/− mice. Cell loss was most pronounced in the outer and inner nuclear layers of Ccl2 −/− /Daf1 −/− mice. The levels of the endoplasmic reticulum chaperone GPR78 and transcription factor ATF4 were significantly increased in the Ccl2 −/− / Daf1 −/− retina. In comparison to the C57BL/6J retina, the phosphorylation of NF-κB p65, p38, ERK and JNK was significantly upregulated while SIRT1 was significantly downregulated in the Ccl2 −/− / Daf1 −/− retina. Our results suggest that loss of Ccl2 and Daf1 causes retinal neuronal death and degeneration which is related to increased endoplasmic reticulum stress, oxidative stress and inflammation. Highlights: Retinas of mice lacking CCL2 and/or DAF1 have higher numbers of autofluorescent foci and apoptotic cells in the ONL and INL. Mice lacking CCL2 and DAF1 have reduced amplitude ERGs and thinned ONL and INL. Retinas of mice lacking CCL2 and DAF1 have elevated levels of GRP78, ATF4, p-ERK, p-JNK, p-p38 and p-NF-κB and decreased SIRT1.